Tinjauan Mendalam Tentang Plagiarisme : Pelanggaran Etika dalam Dunia Akademik dan Profesional - Devia Astry Khairani; Zainarti Zainarti (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
Plagiarism has become a significant issue in both academic and professional contexts, raising questions about intellectual integrity and ethics. This article aims to explore various aspects of plagiarism, including definitions, types, and its impact on scholarly and industry communities. The research methodology involves a comprehensive literature review and analysis of case studies to illustrate the prevalence and motivations behind plagiaristic behaviors. The findings indicate that acts of plagiarism not only harm the individuals involved but also undermine trust and the values of honesty within the academic and professional communities at large. This study also highlights efforts to prevent plagiarism and the importance of ethics education in promoting dignified and respectful writing practices.